2016
DOI: 10.3945/jn.114.202424
|View full text |Cite
|
Sign up to set email alerts
|

Aged Garlic Extract Reduces Low Attenuation Plaque in Coronary Arteries of Patients with Metabolic Syndrome in a Prospective Randomized Double-Blind Study

Abstract: This study indicates that the %LAP change was significantly greater in the AGE group than in the placebo group. Further studies are needed to evaluate whether AGE has the ability to stabilize vulnerable plaque and decrease adverse cardiovascular events. This trial was registered at clinicaltrials.gov as NCT01534910.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 30 publications
1
33
0
Order By: Relevance
“…The initial study sample size was estimated based on MDCTA data showing 24% ± 13% reduction in coronary artery plaque volume with moderate‐dose statin therapy . It is assumed that an 8% reduction in plaque volume (one‐third that seen with statin therapy) would be the minimally important change in noncalcified plaque volume based on past data; multiple studies have shown similar progression/regression rates with different therapies . Further data have been obtained using low‐attenuation plaque volume in both MDCTA and intravascular ultrasound (IVUS) studies.…”
Section: Methodsmentioning
confidence: 99%
“…The initial study sample size was estimated based on MDCTA data showing 24% ± 13% reduction in coronary artery plaque volume with moderate‐dose statin therapy . It is assumed that an 8% reduction in plaque volume (one‐third that seen with statin therapy) would be the minimally important change in noncalcified plaque volume based on past data; multiple studies have shown similar progression/regression rates with different therapies . Further data have been obtained using low‐attenuation plaque volume in both MDCTA and intravascular ultrasound (IVUS) studies.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, prevention of L-type Ca 2+ channels by nifedipine in patients with CAD has led to increased endothelial function and, subsequently, also decreased, though not significantly, the atherosclerotic plaque size in patients with CAD [165]. Moreover, several clinical trials have investigated directly or indirectly the effects of some intervention, related to Ca 2+ , for the treatment of atherosclerosis, as summarized in Table 2 [155,157,158,161,164,165]. For example, in coronary patients undergoing percutaneous intervention, treatment with nifedipine (30-60 mg/day), on top of a statin, for 24 months improved coronary endothelial function [165].…”
Section: Therapeutic Aspectsmentioning
confidence: 99%
“…The American Journal of Cardiology (www.ajconline.org) Semiautomated quantitative CTA was performed per coronary artery segment 11 using QAngio CT software (Research Edition, version 2.1.2; Medis medical imaging systems, Leiden, the Netherlands) as described in previous studies (Figure 1). 12 We excluded vessels with a diameter <1.5 mm. Seven images with severe motion and noise were excluded.…”
Section: Thismentioning
confidence: 99%